Prediction of preterm birth in women with fetal growth restriction – Is the weekly change in sFlt‐1/PlGF ratio or PlGF levels useful? - Jesrine Hong; Kylie Crawford; Erika Cavanagh; Vicki Clifton; Sailesh Kumar (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction To assess the rate of change in soluble fms‐like tyrosine kinase‐1/placental growth factor (sFlt‐1/PlGF) ratio and PlGF levels per week compared to a single sFlt‐1/PlGF ratio or PlGF level to predict preterm birth for pregnancies complicated by fetal growth restriction. Material and methods A prospective cohort study of pregnancies complicated by isolated fetal growth restriction. Maternal serum PlGF levels and the sFlt‐1/PlGF ratio were measured at 4‐weekly intervals from recruitment to delivery. We investigated the utility of PlGF levels, sFlt‐1/PlGF ratio, change in PlGF levels per week or sFlt‐1/PlGF ratio per week. Cox‐proportional hazard models and Harrell's C concordance statistic were used to evaluate the effect of biomarkers on time to preterm birth. Results The total study cohort was 158 pregnancies comprising 91 (57.6%) with fetal growth restriction and 67 (42.4%) with appropriate for gestational age controls. In the fetal growth restriction cohort, sFlt‐1/PlGF ratio and PlGF levels significantly affected time to preterm birth (Harrell's C: 0.85–0.76). The rate of increase per week of the sFlt‐1/PlGF ratio (hazard ratio [HR] 3.91, 95% confidence interval [CI]: 1.39–10.99, p = 0.01, Harrell's C: 0.74) was positively associated with preterm birth but change in PlGF levels per week was not (HR 0.65, 95% CI: 0.25–1.67, p = 0.37, Harrell's C: 0.68). Conclusions Both a high sFlt‐1/PlGF ratio and low PlGF levels are predictive of preterm birth in women with fetal growth restriction. Although the rate of increase of the sFlt‐1/PlGF ratio predicts preterm birth, it is not superior to either a single elevated sFlt‐1/PlGF ratio or low PlGF level.